Photosynthetic Performance and Urea Metabolism After Foliar Fertilization with Nickel and Urea in Cotton Plants - Aguilar, Jailson Vieira [UNESP]; Lapaz, Allan de Marcos [UNESP]; Bomfim, Nayane Cristina Pires [UNESP]; Mendes, Thalita Fischer Santini [UNESP]; Souza, Lucas Anjos; Furlani Júnior, Enes [UNESP]; Camargos, Liliane Santos [UNESP] (MDPI, 2025)
The use of nickel (Ni) as a fertilizer remains a topic of debate, particularly in non-legume species, as Ni is required only in trace amounts for optimal plant function. Urea application in plants, whether foliar or root-based, relies on the urease enzyme to convert urea into NH4+ and CO2, with Ni serving as an essential cofactor. In this study, we conducted an experiment using a 2 × 2 factorial design, combining two urea concentrations [4% and 8% (w/v)] with the absence or presence of Ni (0.3 g L−1 supplied as NiSO4·6H2O). Gas exchange parameters were measured two days after fertilization. We quantified urease enzyme activity, urea content, photosynthetic pigments, carbohydrates, and other nitrogenous metabolites. The presence of Ni during foliar urea fertilization significantly increased the photosynthetic rate and photosynthetic pigments, which we attributed to improved urea assimilation. The combination of urea and Ni enhanced urease activity, leading to higher levels of various nitrogenous metabolites. Ni positively influenced foliar urea assimilation, promoting its conversion into organic compounds, such as proteins, while mitigating the toxic effects associated with urea accumulation.
Keywords: amino acids; chlorophylls; nitrogen; urease